Why do household businesses in Viet Nam stay informal? - Tran Thi Bich; Hai Anh La (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Using unbalanced panel data from the small and medium enterprise surveys in Viet Nam in 2005, 2007, 2009, 2011, 2013, and 2015, this paper investigates factors associated with informality in Viet Nam. We assume that household businesses, especially the top tier firms, become formal either because they perceive benefits of formalization such as an increase in the household performance, or because they want to escape bribes and harassment. Using the random effects model with controlling for the pre-formalization trends, our results show that productive household businesses stay informal because net costs from tax payment may surpass net benefits from formalization. Moreover, government controls do not promote formalization, especially among the "upper" tiers of informal households. Our findings raise a suspicion of collusion corruption between informal households in the top tiers and government tax officials. This opens room for future qualitative and quantitative studies to investigate collusion corruption as a determinant of informality in developing countries.
Keywords: I24; N85; O17; 330; formalization; informal sector; Viet Nam